Pengaruh Metode Struktural Analitik Sintetik (SAS) Terhadap Peningkatan Kemampuan Membaca Awal dan Menulis Awal Kelas 1 SDN Gili Anyar - Eva oktavia; Kusmiyati Kusmiyati (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
The study, titled "The Influence of the Structural Analytic Synthetic (SAS) Method on Improving Early Reading Skills," examines the factors that contribute to students' reading difficulties, including (1) lack of knowledge about letters and (2) inability to understand the meaning of sentences being read. Therefore, the researcher implemented the SAS method as a strategy for early reading instruction. This research employed a quantitative experimental method to improve the reading abilities of first-grade students at SDN Gili Anyar. The study adopted a one-group pre-experimental design, consisting of pre-test and post-test phases. A quota sampling technique was used to select 22 first-grade students as participants. Data were collected through tests and observations, and a z-test was employed to assess the differences in mean scores before and after the intervention. The findings are as follows: 1) The average reading ability of the students before the intervention (pre-test) was 81.37, categorized as sufficient. 2)After the intervention (post-test), the average score improved to 91.17, categorized as very good. 3)The study concludes that the hypothesis (H1) is accepted, indicating that the SAS method effectively enhances the reading skills of first-grade students at SDN Gili Anyar.